A Novel - Morton, Kate; 1976- (New York, 2012)
Withdrawing from a family party to the solitude of her tree house, sixteen-year-old Laurel Nicolson witnesses a shocking murder that throughout a subsequent half century shapes her beliefs, her acting career, and the lives of three strangers from vastly different cultures.
Keywords: England; Fiction; Fiction; Secrecy; Actresses; Social life and customs; Great Britain; Fiction; Mystery fiction